Impact of Inflation on Consumer Spending Habits and its General Implications in Sub-Saharan Africa - Kehinde, Segun (Westscience Press, 2025)
Inflation, as a fundamental economic phenomenon, plays a pivotal role in shaping the economic landscape of regions worldwide. Sub-Saharan Africa, known for its economic diversity and unique socio-economic challenges, is no exception. This essay delves into an exploration of inflation within the context of Sub-Saharan Africa, offering a comprehensive analysis of its dynamics, determinants, and implications. By understanding inflation's multifaceted nature and its impact on the region's socio-economic dynamics, policymakers, economists, and stakeholders can make informed decisions aimed at achieving sustainable economic growth and development.